UMP delegation meets Inspector-General of Police - Abd Rahman, Haji Safie (2021)
KUALA LUMPUR, 22 March 2021 - For the first time, a delegation from Universiti Malaysia Pahang (UMP) led by the Vice-Chancellor, Professor Ir. Dr. Wan Azhar Wan Yusoff paid a courtesy call on the office of the Inspector-General of Police (IGP), YDH Tan Sri Dato’ Seri Abd Hamid Bador.